Effects of kinetin on biological parameters and hemocytes of Achroia grisella (Lepidoptera: Pyralidae) - Çelik, Erinç; Sak, Olga (Archives of Biological Sciences, 2020)
Paper description: Our aim was to improve our understanding of the influence of plant growth regulators on insect biology and physiology. Kinetin effects were examined for the life history traits and hemocytes of Achroia grisella by addition to moth diet or direct injection to the final instars. We show that kinetin can interfere with normal developmental and immune processes of A. grisella by reducing weight, progeny and hemocyte counts. Impairment of the immune system and biological characteristics reveal that kinetin can be used to control this pest, however, long-term harmful effects may develop in both host and parasitoid species. Abstract: The effects of the cytokinin hormone kinetin on the life history traits and hemocytes of the smaller wax moth Achroia grisella F. (Lepidoptera: Pyralidae) were examined in order to better understand the physiological impacts of plant growth regulators on insects. Based on the obtained results, it was found that kinetin did not lead to significant changes in larval mortality, development time, morphological disorders and egg fertility. Female and male longevity were almost unchanged when early instars were fed with a kinetin-added diet, and it tended to be higher for males when kinetin was applied at the egg stage, especially at 5 mg/L. The weight of females decreased significantly with 25 and 3000 mg/L of kinetin and that of males with 5 mg/L. The most striking effect was a considerable decline in the number of progeny, particularly at 400 and 3000 mg/L, as compared to the control. The injection of kinetin caused noticeable decreases in the number of hemocytes in the circulation at 3 and 24 h. This work presents the first evidence that kinetin adversely affects the development and the hemocyte counts of an economically-important host species, A. grisella. https://doi.org/10.2298/ABS200107012C Received: January 7, 2020; Revised: March 20, 2020; Accepted: March 27, 2020; Published online: April 8, 2020 How to cite this article: Çelik E, Sak O. Effects of kinetin on biological parameters and hemocytes of Achroia grisella (Lepidoptera: Pyralidae). Arch Biol Sci. Arch Biol Sci. 2020;72(2):181-92.